Case report: Artificial thymic organoids facilitate clinical decisions for a patient with a TP63 variant and severe persistent T cell lymphopenia - Gall, Alevtina; Bosticardo, Marita; Ma, Stacey; Chen, Karin; Amini, Kayla; Pala, Francesca; Delmonte, Ottavia M.; Wenger, Tara; Bamshad, Michael; Sleasman, John; Blessing, Matthew; van Oers, Nicolai S. C.; et al. (Frontiers in Immunology, 2024)
Pathogenic variants in the transcription factor TP63 are associated with clinically overlapping syndromes including ectrodactyly-ectodermal dysplasia clefting (EEC) and ankyloblepharonectodermal defects-cleft lip/palate (AEC). T cell lymphopenia has rarely been described in individuals with TP63 variants and the cause of the T cell defect is unclear. Here, we present a case of a female infant born with TP63-related syndrome and profound T cell lymphopenia, first uncovered through newborn screening. Flow cytometry analysis revealed low CD4+ naïve T cells and nearly absent CD8+ T cells with intact B and NK cell compartments. A de novo heterozygous pathogenic variant c.1040 G>A (C347Y) in exon 8 of TP63 was identified. An artificial thymic organoid system, to assess the intrinsic ability of the patient's hematopoietic cells to develop into T cells, was performed twice using separate peripheral blood samples. Ex vivo T cell differentiation was evident with the artificial organoid system, suggesting that a thymic stromal cell defect may be the cause of the T cell lymphopenia. Consistent with this, interrogation of publicly available data indicated that TP63 expression in the human thymus is restricted to thymic epithelial cells. Based on these data, congenital athymia was suspected and the patient received an allogenic cultured thymus tissue implant (CTTI). This is the first report of suspected congenital athymia and attempted treatment with CTTI associated with TP63 variant. At 9 months post-implant, peripheral lymphocyte analysis revealed measurable T cell receptor excision circles and presence of CD4+ recent thymic emigrants suggestive of early thymopoiesis. She will continue regular monitoring to ensure restoration of T cell immunity.